2014
DOI: 10.1016/j.jmb.2013.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Aggregation of the Insulin-Derived Steric Zipper Peptide VEALYL Results in Different Aggregation Forms with Common Features

Abstract: Recently, several short peptides have been shown to self-assemble into amyloid fibrils with generic cross-β spines, so-called steric zippers, suggesting common underlying structural features and aggregation mechanisms. Understanding these mechanisms is a prerequisite for designing fibril-binding compounds and inhibitors of fibril formation. The hexapeptide VEALYL, corresponding to the residues B12-17 of full-length insulin, has been identified as one of these short segments. Here, we analyzed the structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 74 publications
(162 reference statements)
4
18
1
Order By: Relevance
“…Solid-state NMR spectroscopy in combination with atomistic MD simulations in recent work 63 reveal that VEALYL peptides arrange in antiparallel β-sheets stacked parallel in a steric zipper structure. These authors have identified several aggregated states: disordered oligomeric, microcrystalline and fibrillar.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Solid-state NMR spectroscopy in combination with atomistic MD simulations in recent work 63 reveal that VEALYL peptides arrange in antiparallel β-sheets stacked parallel in a steric zipper structure. These authors have identified several aggregated states: disordered oligomeric, microcrystalline and fibrillar.…”
Section: ■ Discussionmentioning
confidence: 99%
“…7 and supplemental Table S2) along seven consecutive residues in the insulin B chain ( 11 LVEALYL 17 ). This aggregation prone sequence is believed to be one of the driving forces behind insulin fibrillization as it forms a energetically favorable steric zipper in the insulin amyloid fiber (51,52). Several neighboring residues such as His-10, Cys-19, Gly-20, Glu-21, Gly-23, Phe-24, and Thr-27 in the B chain as well as a few residues in the A chain, namely Ser-12, Leu-13, Leu-16, Tyr-19, and Cys-20, also display substantial CSPs (supplemental Table S2).…”
Section: Kr7 Binds Both Free Insulin and Insulin Fibers In The Low MImentioning
confidence: 99%
“…Transition of monomers to stable aggregates is accompanied by de-solvation of non-polar residues to form the amyloid core. 43,44 Such transition can be monitored by changes in hSAS along the reaction coordinate. 44 In control, the observation of a steep drop in hSAS within 50 ns was indicative of early burial of monomer side chains through hydrophobic interactions followed by a gradual decline till the end of simulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These observations complied with earlier experimental and theoretical reports documented on aggregation of short peptides. 18,20,43,44,52 FEL projections indicated spontaneous association of monomers to form higher order ensembles whereas an early single large basin was observed in FEL of IAP (22)(23)(24)(25)(26)(27)(28) and AGel (186-192) monomeric transitions into assembly in the presence of intercalators. Apparently, the kinetics of assembly formation in the presence of compounds was driven further owing to some topological advantage imparted by their planar groups.…”
Section: Discussionmentioning
confidence: 99%